Analysis of Farmers' Knowledge Level of Off Season Cultivation Technology, Harvesting Techniques, Post Harvest Handling and Quality of Gedong Gincu Mango Fruits for the Export Market - Abirizal Alfarisi; Syahrul Maulana; Dwi Purnomo; Dodi Budirokhman (Pusat Publikasi Nusantara, 2024)
Gedong gincu mango is a food commodity that has good added value with relatively high demand in various markets. Thus, production availability and quality standards can be realized by implementing off season gedong gincu mango cultivation, harvesting and post-harvest techniques that can minimize the level of losses due to improper handling. This research aims to determine the level of farmers' knowledge regarding off season cultivation, harvest techniques, post-harvest handling and fruit quality for the export market. The research was conducted in Sedong District with the consideration that this area is the highest mango production center in Cirebon Regency. The research is planned to be carried out in January 2024. The research design used is descriptive quantitative with survey research techniques. The sample in this study was 54 gedong gincu mango farmers. The data analysis technique was carried out using descriptive statistics with score weighting between 1 and 5. The results of the analysis showed that the level of knowledge of farmers in off season cultivation was 84.86%, harvest techniques were 82.90% and post-harvest handling was 82.04%. so it is classified as very knowledgeable, while farmers' knowledge of the quality of export fruit is 79.77%, so it is classified as knowledgeable.